Hymenopterous parasitoids of Dasiops (Diptera: Lonchaeidae) infesting cultivated Passiflora spp. (Passifloraceae) in Cundinamarca and Boyaca, Colombia (2016)
Dasiops spp. are the most important pest in cultivated Passiflora plants. Larvae of these fruit flies are herbivores, feeding on flower buds and fruit of yellow passionfruit, sweet granadilla, banana passionfruit and purple passionfruit crops located in Cundinamarca and Boyaca, Colombia. Geographic distribution, natural abundance and percentage of parasitoidism for every Dasiops species by each plant species were determined. Aganaspis pelleranoi (Hymenoptera: Figitidae) was found to be a parasitoid of D. inedulis (14.19-50.00%), infesting flower buds of yellow passionfruit and fruit of sweet granadilla (7.41%). Microcrasis sp. (Hymenoptera: Braconidae) was found to be parasitizing both D. gracilis (0.83-3.13%) and D. inedulis (0.83%) in purple and yellow passionfruit. Trichopria sp. and Pentapria sp. (Hymenoptera: Diapriidae) were found to be parasitizing D. inedulis (40.00% and 4.17-20.00%, respectively) and D. gracilis (1.69-22.22% and 1.67-29.17%, respectively) in purple passion fruit. Dasiops caustonae was found to be infesting banana passionfruit only in Boyaca, naturally parasitized by Pentapria sp. (11.11-33.33%). Because Pentapria sp. had a wide geographical distribution as an idiobiont of Dasiops spp. pupae, in all of the assessed cultivated Passiflora species, despite a high selection pressure by chemical control distributed at regular calendar intervals, it would be a crucial strategy in pest management control. Collecting fallen flower buds and fruit infested by Dasiops spp. is important to truncate the life cycle of fruit flies and allow emergence of parasitoids. This simple cultural strategy could have important implications in reducing production costs, increased crop yields and environmental care.